C. Cohen-Skalli, Don Isaac Abravanel: An Intellectual Biography - Lelli, Fabrizio (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2021)
Recensione